PERAN ABDUL KHOLIK (ANGGOTA DPD RI DAPIL JAWA TENGAH PERIODE 2019-2024) DALAM PEMBANGUNAN JAWA TENGAH - Ali Mushon; Ali Martin; Agus Riyanto (Public Sphere: Jurnal Sosial Politik, Pemerintahan dan Hukum, 2026)
This study is motivated by the suboptimal distribution of development in Central Java, as reflected in issues of poverty, regional disparities, human resource quality, unemployment, connectivity, and local economic empowerment. The study aims to analyze the role of Abdul Kholik as a Regional Representative Council (DPD RI) member representing Central Java for the 2019–2024 term in advocating regional development. This research employs a phenomenological approach using an intellectual biography research design. Data were collected through observation, interviews, and documentation, and were analyzed through the stages of data collection, data reduction, data display, and conclusion drawing/verification. The findings indicate that Abdul Kholik played an active role as a regional representative by accommodating public aspirations, advocating policies, monitoring development, and serving as a liaison between regional interests and the central government. His efforts focused on equitable development, strengthening connectivity, empowering villages, promoting micro, small, and medium enterprises (MSMEs), and optimizing regional potential through the Three Economic Corridors initiative. These contributions have reinforced area-based development that is more inclusive, integrated, equitable, and sustainable, while enhancing Central Java’s bargaining position in national policymaking. ABSTRAKPenelitian ini dilatarbelakangi oleh belum optimalnya pemerataan pembangunan di Jawa Tengah yang ditandai dengan persoalan kemiskinan, ketimpangan wilayah, kualitas sumber daya manusia, pengangguran, konektivitas, dan pemberdayaan ekonomi lokal. Kajian ini bertujuan menganalisis peran Abdul Kholik sebagai Anggota DPD RI Daerah Pemilihan Jawa Tengah periode 2019–2024 dalam memperjuangkan pembangunan daerah. Penelitian menggunakan pendekatan fenomenologi dengan jenis penelitian intellectual biography. Data diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis melalui tahapan pengumpulan data, reduksi, penyajian, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Abdul Kholik berperan aktif sebagai representasi daerah melalui penyerapan aspirasi, advokasi kebijakan, pengawasan pembangunan, dan penghubung kepentingan daerah dengan pemerintah pusat. Fokus perjuangannya mencakup pemerataan pembangunan, penguatan konektivitas, pemberdayaan desa, pengembangan UMKM, serta optimalisasi potensi wilayah melalui gagasan tiga poros ekonomi. Peran tersebut berimplikasi pada penguatan pembangunan berbasis kawasan yang lebih inklusif, terintegrasi, berkeadilan, dan berkelanjutan